Edukacyjna rola i znaczenie współczesnego polskiego teatru emigracyjnego w Wielkiej Brytanii - Kama Pawlicka (Facta Simonidis)
This article analyses the educational role and significance of Polish émigré theatre in Britain, particularly in London. This phenomenon has received limited scholarly attention, with only few articles addressing its history or individual theatres. Therefore, it is important to explore in greater depth the substantial educational contribution of émigré theatre to the Polish community. This study contributes to the ongoing academic discourse on the theatrical heritage of Polish migrants worldwide, conducted at the Universities of Łódź, Opole, and Warsaw. The analysis draws upon existing data, original research, including numerous enquiries conducted in Poland and Great Britain, and in-depth interviews undertaken as part of a Ministry of Culture and National Heritage scholarship for the popularisation of culture.